Aqueous-Phase Partial Oxidation of Methane over Pd-Fe/ZSM-5 with O2 in the presence of H2 - 양건식 (The Graduate School, Ajou University, 2024)
Methane is a major component in natural gas, shale gas, coalbed gas, biogas, and gas hydrates, which are available in abundance. Additionally, it is used as a chemical feedstock via syngas (a mixture of CO and H2) in an energy-intensive process. Such commercial application requires the use of large-scale manufacturing plants. Thus, there is a demand for a process that enables the direct conversion of methane under mild reaction conditions. Partial oxidation of methane to methane oxygenates with molecular oxygen is an ideal route for the direct methane conversion technique as it is thermodynamically favorable even at low reaction temperatures. In the pursuit of this objective, numerous oxidizing agents have been employed in the reaction. However, except for oxygen, many of these oxidants are often regarded as economically impractical. A catalytic system that oxidizes methane to methane oxygenates using H2O2 generated in-situ could be of the solutions. In this study, we have developed a one-body catalyst composed of Pd-Fe/ZSM-5, containing a low concentration of palladium, for the selective aqueous-phase oxidation of methane in the presence of H2 and O2. The palladium metal component facilitated the synthesis of H2O2, which then reacted with methane over the nearby iron species located within the zeolite pores. Remarkably, 0.28%Pd-0.56%Fe/ZSM-5 displayed excellent productivity of c.a. 30 mmol kgcat-1 h-1 and methane oxygenates selectivity of 70% in a continuous flow reactor. *Keyword: hydrogen peroxide, methanol, partial oxidation of methane, Pd-Fe/ZSM-5, stability.
학위논문(석사)--에너지시스템학과,2024. 2
Keywords: Pd-Fe/ZSM-5; hydrogen peroxide; methanol; partial oxidation of methane; stability